Created in the image of God? Progressive social services and faith-based organizations. Issue 3 (2nd September 2021) - Parsell, Cameron; Hutchins, Marcus; Simpson Reeves, Laura; Deighton, Chris
ABSTRACT: There are concerns that religion in state-funded social services for people experiencing poverty can lead to discrimination, proselytizing, and moralism. The welfare state ideals of universalism and comprehensiveness sought to overcome limitations of social services provided by faith-based organizations. Against the backdrop of the secular welfare state theories—albeit often unrealized—and concerns that faith in social services leads to exclusion, this article demonstrates how evangelical faith can drive progressive social services. Drawing on ethnographic research in Australia, the article illustrates how commitment to the doctrine that all people are created in the image of God shapes a model of social service where faith is explicitly positioned to disrupt distinctions between the moral and the immoral. Our analysis demonstrates how faith is used to challenge the assumption that people's behaviors reflect their values, aspirations, and identities. Faith drives and justifies non-exclusionary social service provision.